Effect of Open Spaces in Residential Complexes on the Social Interactions of Inhabitants - Khaleghimoghaddam Navid (Architecture, Civil Engineering, Environment)
The recent growth of urbanisation has increased the demand for mass housing and led to a decline in design quality and attractiveness. The design of contemporary residential complexes has posed serious problems for the personal and social life of residents because it has not taken into account human needs and psychological consequences. This includes neglecting the relationship between social interactions and physical factors. The aim of the present study is to investigate the relationship between open spaces and social interactions in the design of residential complexes. It was carried out through field studies and surveys. After explaining the different aspects of the importance of social relationships between people, the effects of open spaces on the social interactions of residents in three residential complexes in Tabriz, Iran, were investigated. The results show that factors such as the social homogeneity of residents and the use of design patterns to create safe, attractive and comfortable conditions for the presence of families in the open spaces of the complex have a significant effect on increasing the social interactions of neighbours.